Bibliographical review and analysis of visualizations about Kingsleya attenboroughi Pinheiro & Santana, 2016 (Crustacea: Decapoda: Brachyura: Pseudothelphusidae) (Research, Society and Development, 2021)
Kingsleya attenboroughi, popularly known as “Guajá”, is a species of freshwater crab, endemic to Chapada do Araripe- Ceará, Brazil (predominantly located in the district of Arajara- Municipality of Barbalha), a region characterized by numerous sources of fresh water, and thus favoring ideal conditions for the survival of K. attenboroughi in the locality. This research consists of a survey of data about the species, and different scientific bases were analyzed: Google academic®, ScienceDirect®, Web of sciences®, and Pubmed® to obtain the information. K. attenboroughi differs mainly from its counterparts in that it has its own characteristics, such as a short apical plate in the first gonopod. Few studies have been reported to date. Its ecology worries scholars as it is under constant threat of extinction. In this way, incentives and research have been growing in this region to avoid the collapse of biodiversity.